China's changing diet and its impacts on greenhouse gas emissions: an index decomposition analysis. (29th November 2017) - Hawkins, Jacob; Ma, Chunbo; Schilizzi, Steven; Zhang, Fan
Abstract : With increasing awareness of agriculture's contribution to global greenhouse gases (GHGs) and China's position as the world's top GHG emitter, there is heightened attention to the embodied emissions in China's food consumption. China's diet has shifted to include more fruit, vegetables, meat and dairy. Not surprisingly, GHG emissions from food consumption have also increased substantially. This analysis links China's food consumption with the emissions of food production industries in China and its trade partners to determine the effects of dietary change on GHGs since 1989. We utilise high‐resolution food production and emissions data to perform a logarithmic mean Divisia index decomposition to attribute changes in GHG emissions to the scale, supply structure, demand structure and efficiency effects resulting from Chinese dietary changes over a 20‐year period. This study finds that while countries supplying food to China contribute little to China's food‐related GHGs, demands for meat and dairy play a much larger role, driving up emissions. The overall scale of increased consumption of all food further propels growth in GHG emissions. Results indicate, however, that while food consumption in China more than doubles between 1989 and 2009 improvements in technological efficiency limit the rate of increase.